Citizen, Subject, Human: For A Humanist Sociology at The End of The Eurocene. Issue 2 (May 2023) - Nicholls, Heidi
The history of humanism is intertwined with empire and racism. Many in sociology are aware of the significant contributions of Sylvia Wynter in our understanding of how modernity has shaped what it means to be human. 'Man, ' Wynter argues, was never more that the European bourgeois man of the colonial world. Colonial conceptions of humanity have largely excluded ways of being and living that resist and refuse global empires. I argue that the differences between those who lived under state rule and those whose politics were illegible to European colonists became part of what we now think of as race. Colonists conflated the human with a certain kind of colonial subject, and later, the favored White citizen-subject and fellow colonist of an empire-state. In contemplating this journal's title and mission for a humanist sociology, I argue that 'society' its 20 th and 21 st century articulations have often stood in for Man in the Wynterian sense. U.S. Sociology promoted 'society' as both an object of inquiry and a cognate for the colonial state. As such, sociology as the study of 'society' contained a specifically statist bent. Finally, this essay ends by offering examples of anticolonial humanist sociology that nurtures a more egalitarian genres of the human for the future.